The Eminent Admiral and Scientist - Minasyan, Edik; Harutyunyan, Kliment (History and Culture, 2025)
Summarizing our study about Ivan (Hovhannes) S. Isakov (Ter-Isahakyan), a talented commander and admiral of the Soviet Union’s Armed Forces and Navy, a distinguished representative of the Armenian people, a hero of the Soviet Union, we come to the conclusion that he was not only an outstanding naval and military figure, but also a famous scientist and writer. I. S. Isakov lived 73 years. 53 of his life he devoted to the sacred cause of protecting the motherland. Born and raised in Hajikend village of Elizavetpol Getashen region (Elizavetpol Governorate, Northern Artsakh). He received a high-quality education. He graduated from the Naval Academy, joining the ranks of the Red Army Navy, actively participated in the civil war, as a warship commander, served in the Baltic and then the Black Sea Fleet. Throughout his career he occupied the positions of commander, chief of staff, 1st deputy of the People’s Commissariat of Navy of the USSR. Having participated in the Soviet-Finnish and then the Great Patriotic War, Admiral I. S. Isakov made a serious contribution to the heroic defense of Leningrad, distinguished himself in the battles for the Crimea and the Caucasus, where he was wounded and lost his leg. After recovery, he continued to serve, holding responsible positions. After the victory, he actively engaged in scientific work. In 1950 and 1953, two volumes of the valuable work “The Marine Atlas” were published under his authority, which were awarded the Stalin Prize of the 1st category. From 1958 until the end of his life, 11 October 1967, Admiral Isakov was the chief inspector of the group of chief inspectors of the Ministry of Defense of the USSR. In 1955 he was awarded the title of Admiral of the USSR Navy, and in 1965 he was awarded the title of Hero of the Soviet Union. I.S. Isakov has written 170 scientific works. He was awarded the degree of Doctor of Naval Sciences in 1946. In 1958, he was elected a corresponding member of the Academy of Sciences of the USSR.The motherland highly appreciated the merits of the outstanding admiral, in addition to the title of hero, awarding him with 6 orders of Lenin, 3 orders of the Red Banner, 2 orders of the 1st rank of Ushakov, etc. In Armenia, one of the main streets of Yerevan is named after Admiral Isakov, where his monument was erected. The primary school N 132 in Yerevan was named after him, and the admiral’s museum was opened next to it. The RA government founded the “Admiral Isakov” medal, which is one of the government’s highest honorary awards.
Keywords: Admiral; fleet; national hero; First World War; cruiser; sea; army; defense; front; sailor